Differential gene expression in sugar cane infected by leifsonia xyli subsp. Xyli - Tiraboschi Ferro, Maria Inês [UNESP]; De Barros, Neli Martins [UNESP]; Dabbas, Karina Maria [UNESP]; De Laia, Marcelo Luiz [UNESP]; Kupper, Katia Cristina [UNESP]; De Moraes, Vicente Alberto; De Oliveira, Julio Cezar Franco [UNESP]; Ferro, Jesus Aparecido [UNESP]; Zingaretti, Sonia Maria [UNESP] (My University, 2007)
The macroarray nylon membrane technology was used to study the differential gene expression of 3.575 ESTs clones from sugarcane libraries. Total RNA was extracted from two varieties, one known as tolerant (SP80-0185) and another known as susceptible (SP70-3370) to the ratoon stunting disease (RSD), after being inoculated with Lefsonia xyli subsp. xyli bacterial extracts, and used as probe. Out of the 3.575 ESTs, 49 showed differential expression levels. Most of the selected ESTs were found in the resistant variety, 41 being induced and 3 being repressed in response to bacterial inoculation. On the other hand, the susceptible variety showed only 5 differentially expressed genes, 2 being induced and 3 being repressed. These results indicate that the tolerance to bacterial infection could be associated to extracellular signal perception because ESTs associated to signal transduction pathways were induced in the variety SP80-185, e.g. plasma membrane H+ ATPase EST. Also, ESTs related to transcription factor expression, such as G-box, OsNAC6, “DNA binding”, MYB family, Zinc Finger were induced in the tolerant variety after infection. An EST with high similarity to G-Box binding factor, a cis-DNA sequence present in some plant promoter genes required to signal transduction for environmental signals, was also induced. Even though the susceptible variety had no significant difference in gene expression, a lipase-like EST was repressed when plants were infected. Lipase, a membrane enzyme, is also involved in jasmonate biosynthesis, which plays a major role in plant defense mechanisms. Putative roles for induced and repressed genes in both tolerant and susceptible varieties are discussed here.
Análise do perfil de expressão dos genes da cana-de-açúcar envolvidos na interação com Leifsonia xyli subsp. Xyli
Keywords: CDNA macroarray; Plant-pathogen interaction; Ratoon stunting disease; Sugarcane